Simplified Reaction Mechanisms for the Oxidation of Jet Fuel - Song, Shubao; Wang, Cheng; Shao, Jiankun (Combustion science and technology, 2024)
Jet fuel is a complex mixture comprising thousands of components, which poses challenges for conducting kinetic simulations on its oxidation process. To address this issue, the HyChem (hybrid chemistry) approach has recently been proposed as an effective method for modeling the oxidation of real multicomponent fuels. Nevertheless, the simplest HyChem approach still involves 31 species and more than 100 reactions, presenting a significant challenge for computational fluid dynamics (CFD) simulations of real multicomponent fuels. In order to enhance the computational efficiency and affordability of numerical simulations for reactive flow, this study developed three simplified mechanisms, namely S66 (28 species and 66 reactions), S8 (12 species and 8 reactions), and S2 (5 species and 2 reactions), which depict the high-temperature (T = 1000～1470 K), high-pressure (P > 1.0 atm), and fuel-lean (φ < 0.7) oxidation of real multicomponent jet fuels inspired by the HyChem methodology and single-step overall reaction. The accuracy of the mechanisms was validated using experimental data, including ignition delay times and laminar flame speed from the literature. Notably, the CPU time required for the simplest HyChem model is longer than 20 times that of the S2 mechanism under identical conditions in the CFD simulation example. This is due to the highly simplified approach of the S2 mechanism. Consequently, the S2 mechanism is expected to be applicable in combustion kinetic simulations in complex environments such as combustion chambers because of its high computational efficiency and relative accuracy.